Scope, Standards, and Signals: ESG Assurance and Profitability under Indonesia’s Evolving Disclosure Regime - Noviana, Ita; Hamdah, Dida Farida Latipatul (Summa : Journal of Accounting and Tax, 2024)
This study investigates the impact of ESG (Environmental, Social, and Governance) assurance and disclosure quality on the financial performance of companies listed in the IDX ESG Leaders Index in Indonesia. Motivated by regulatory advances such as POJK 51/2017 and the adoption of SPK Indonesia aligned with IFRS S1 and S2, the research assesses whether comprehensive and credible ESG disclosures enhance Return on Equity (ROE) and reduce cost of capital. Using panel data for Q1 2024 and a balanced sample of 30 firms, the analysis examines ESG disclosure indicators Scope 1, 2, and 3 emissions, third party assurance, governance structures, and reference to global standards (GRI, ISSB) and their associations with ROE, excess returns, and cost of debt. Panel regression results show that firms with ESG assurance exhibit significantly higher ROE. Scope 3 emissions disclosure and alignment with ISSB also correlate with reduced financing costs. Robustness tests confirm the stability of results. The findings demonstrate that ESG assurance acts as a signal of credibility, mitigates greenwashing risk, and enhances market perception. Companies with strong ESG governance and transparent, standardized disclosures are more likely to attract investment and secure favorable financing terms. As Indonesia moves toward mandatory ESG assurance through SPK Indonesia, this research supports regulatory emphasis on verifiability and standard alignment. The study contributes localized empirical evidence from a leading Southeast Asian market and informs policy design, investor strategy, and corporate governance practices under evolving ESG disclosure standards.